Tackling addictive behaviors through memory suppression: A scoping review and perspective. - de Almeida‐Antunes, Natália Alexandra; Sampaio, Adriana Conceição Soares; Crego, Manuel Alberto Barreiro; López‐Caneda, Eduardo Guillermo (Alcohol, Clinical & Experimental Research, 2024)
Forgetting is often viewed as a human frailty. However, over the years, it has been considered an adaptive process that allows people to avoid retrieval of undesirable memories, preventing them from suffering and discomfort. Evidence shows that the ability to suppress memories is affected by several psychopathological conditions characterized by persistent unwanted thoughts, including anxiety and posttraumatic stress disorders. Nevertheless, memory suppression (MS) mechanisms in addiction—a clinical condition characterized by recurrent drug‐related thoughts that contribute to repeated drug use—have received little attention so far. Addiction theories reveal that drugs change behavior by working on memory systems, particularly on declarative memory, which is related to the retrieval and encoding of drug‐related memories. In this review, the main behavioral and neurofunctional findings concerning the Think/No‐Think task—an adaptation of the classical Go/No‐Go tasks typically used to evaluate the suppression of motor response—are presented. We then show how the memory system can be involved in the craving or anticipation/preoccupation stage of the addiction cycle. Subsequently, the study of MS in the context of addictive behaviors is highlighted as a promising approach for gaining knowledge about the mechanisms contributing to the continuation of addiction. Finally, we discuss how interventions aiming to strengthen this ability could impact the anticipation/preoccupation stage by (i) reducing the accessibility of drug‐related memories, (ii) decreasing craving and attention toward drug‐related stimuli, and (iii) improving overall inhibition abilities. In conclusion, this review aims to illustrate how the study of MS may be a valuable approach to enhance our understanding of substance use disorders by unveiling the underlying cognitive and neural mechanisms involved, which could have important implications for addiction treatment.